2014
DOI: 10.5145/acm.2014.17.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical Wound Infection Caused byMycobacterium conceptionenseIdentified by Sequencing of 16S rRNA,hsp65, andrpoBGenes in an Immunocompetent Patient

Abstract: Rapidly growing mycobacteria are ubiquitous in the environment and are increasingly being recognized as opportunistic pathogens. Recently, a new species, Mycobacteium conceptionense, has been validated from the Mycobacterium fortuitum third biovariant complex by molecular analysis. However, there are few reports, and postsurgical wound infection by this species is rare. We report a case of postsurgical wound infection caused by M. conceptionense in an immunocompetent patient that was identified by a sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In 2006, Adekambi et al ( 12 ) reported that the bootstrap value of the rpoB gene sequence for the fast-growing Mycobacterium group, in both the M. smegmatis-goodii cluster and the M. fortuitum-houstonense cluster, was 100%. Lee et al ( 32 ), in 2014, identified that NTM performed rpoB , 16srRNA , and hsp65 gene sequencing. The results showed that, based on the sequence of the 16SrRNA gene, isolates were indistinguishable and unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Adekambi et al ( 12 ) reported that the bootstrap value of the rpoB gene sequence for the fast-growing Mycobacterium group, in both the M. smegmatis-goodii cluster and the M. fortuitum-houstonense cluster, was 100%. Lee et al ( 32 ), in 2014, identified that NTM performed rpoB , 16srRNA , and hsp65 gene sequencing. The results showed that, based on the sequence of the 16SrRNA gene, isolates were indistinguishable and unidentified.…”
Section: Discussionmentioning
confidence: 99%